Rancang Bangun Sistem Informasi Perpustakaan Berbasis Web Pada SMAN 10 OKU - Vina Anjelia; Abdul Rahman; Destriarini Destriarini (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2023)
The library is a facility that supports student and teacher learning activities. The library collection is in the form of textbooks that are used as references during the learning process. The Library of SMA Negeri 10 OKU Regency South Sumatra uses traditional methods in managing data and information. This hinders librarians to process data and present information effectively. The purpose of this research is to design a web-based library information system to assist libraries in solving school library problems. Observations, interviews and literature studies are the methods used to collect data (needs analysis). The prototype is used to build a school library information system. The results of the school library information system design were tested using black box testing. The results of the system activity data, the designed school library information system and the results of the information system evaluation. Activity data is shown in the analysis of running systems. The information system design is displayed with business processes, UML diagrams, and web-based information system screen displays. The evaluation results show that the school library information system can quickly query data, and the information displayed in reports is accurate.